1995
DOI: 10.5144/0256-4947.1995.579
|View full text |Cite
|
Sign up to set email alerts
|

A Study of 875 Cases of Thyroid Cancer Observed Over a Fifteen-Year Period (1975–1989) at the King Faisal Specialist Hospital and Research Centre

Abstract: Thyroid cancer (TC) is a common malignancy encountered at King Faisal Specialist Hospital and Research Centre (KFSH&RC). Of 19,885 different malignant tumors seen during the period from 1975 to 1989, there were 875 cases (4.4%) of TC. Of 1374 tumors of endocrine glands seen during the same period, 67% were thyroid neoplasms. TC represented 7.5% (618 cases) of all neoplasms in the females, second only to breast cancer. All types of TC were seen, with papillary thyroid carcinoma (PC) being the most common (79%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
14
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
6
14
1
Order By: Relevance
“…Concerns about a rising rate of affliction are especially high when the disease is cancer. It is of interest, then, to learn that Ahmed and colleagues 1 report that the incidence of thyroid cancer is increasing at the King Faisal Specialist Hospital and Research Centre (KFSH&RC), where a large number of the patients with serious thyroid disorders in Saudi Arabia are referred.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns about a rising rate of affliction are especially high when the disease is cancer. It is of interest, then, to learn that Ahmed and colleagues 1 report that the incidence of thyroid cancer is increasing at the King Faisal Specialist Hospital and Research Centre (KFSH&RC), where a large number of the patients with serious thyroid disorders in Saudi Arabia are referred.…”
mentioning
confidence: 99%
“…The authors also note that other investigators 2 have found the annual incidence of all cancers in Saudi Arabia to be 80 per 100,000 or about 800 per million population. Based on a population of 10 million in the country, 1 there would be 8000 patients who developed cancer each year, and assuming that the relative frequency of thyroid cancer is similar to that at KFSH&RC, then 4% x 8000 gives an incidence of 320 patients per year developing thyroid cancer in all of Saudi Arabia. In the latest period studied, the national annual rate of thyroid cancer calculates to be 32 per million.…”
mentioning
confidence: 99%
“…15 This may explain the high incidence of PC recently reported, especially in females. 14,15 The high relative frequency of thyroid carcinoma in the Al-Qassim region is in contrast to other parts of the Kingdom. 5,6,8,9 Other little understood contributing factors responsible for the high relative frequency of thyroid carcinoma in this region need to be explained.…”
Section: Discussionmentioning
confidence: 98%
“…The median age at diagnosis of 39 years in females and the peak incidence in the 21-30-year age group is similar to the data from Riyadh. 12,14 Papillary carcinoma (PC) was more frequent than the follicular type. The marked predominance of PC that we saw has been noted in many other series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation